The Effect of Regional Own-source Revenue, Tax Revenue-sharing Fund, General Allocation Fund and Special Allocation Fund to the Human Development Index (Based on the Study of Provincial Government in Indonesia) - Mutiha, A H (KnE Social Sciences, 2018)
The purpose of this study is to examine the effect of Regional Own-source Revenue, Tax Revenue-sharing Fund, General Allocation Fund and Special Allocation Fund to Human the Development Index (HDI). The HDI is used as a benchmark to assess the performance of provincial governments in terms of providing public services. Population in this research is all Provincial Government in Indonesia and the data used is Provincial Government financial data of 2013, 2014, and 2015, which were analyzed using multiple regression. The results of this study show that the Regional-own Source Revenue has a significant positive impact on the Human Development Index, while the Tax Revenue-sharing Funds, General Allocation Funds and Special Allocation Funds have significant negative impacts on the Human Development Index. Keywords: Regional-own Source Revenue, Tax Revenue-sharing Funds, General Allocation Funds and Special Allocation Funds, Human Development Index